Vzroki za nastanek šoka in osnovne terapevtske smernice - Hribar-Habinc, Miša (Obzornik zdravstvene nege, 1980)
The author gives the latest definition of shock and describes the etiopathogenetic and aptophysiologic features of various shock conditions. He presents in detail four stages of the hypovolemic shock, referring to the pathophysiologic processes and clinical picture. He points to the "time factor", which is of primary importance in successfull management of shock conditions. Next, he deals with the indices for the estimate of microcirculation in the shocked organism as well as the fundamental guidelines of the shock management.